Freedom church of the poor: Martin Luther King Jr.'s Poor People's Campaign - Wessel-McCoy, Colleen (Lexington Books/Fortress Academic, 2021)
King's vision for a campaign of the poor -- Organizing a new and unsettling force -- The poor come to Washington -- Assessing the campaign -- Theologies of the PPC -- King's theological ethics -- Movement as church -- Freedom church of the poor today.